Implementasi Pembuatan Sumur Resapan Air Untuk Penanggulangan Banjir Di Kota Pekanbaru Berdasarkan Peraturan Daerah Nomor 10 Tahun 2006 Tentang Sumber Daya Air Dan Sumur Resapan - Hendri, Hendri; Ardiansah, Ardiansah; fahmi, sudi (JURNAL TERAPAN PEMERINTAHAN MINANGKABAU, 2024)
Regional Regulation Number 10 of 2006 contains policies regarding the obligation to build infiltration wells, it is clearly regulated that the obligation to construct infiltration wells is addressed to every person in charge. Responsible for the construction covering the ground surface and the number of infiltration wells made in accordance with the total land surface covered by the building. This rule is contained in Article 19 paragraph (4) of Regional Regulation Number 10 of 2006 which reads: "Every building that has been established and does not yet have an infiltration well is obliged to make a follow-up infiltration well". Region Number 10 of 2006 concerning Water Resources and Infiltration Wells is not implemented properly, there are still many building owners in Pekanbaru City who do not build infiltration wells. Barriers to the implementation of the construction of water infiltration wells in Pekanbaru City are the low level of public knowledge, lack of supervision and no sanctions and efforts to overcome obstacles to the implementation of water infiltration wells for flood prevention in Pekanbaru City based on Regional Regulation Number 10 of 2006 concerning Water Resources and Wells. The absorption is to carry out socialization and legal counseling, improve supervision and cooperate with related agencies.